Taxonomic position of Odocnemis steindachneri in the tribe Helopini (Coleoptera: Tenebrionidae) - Nabozhemko, Maxim (ENTOMOLOGIA HELLENICA, 2025)
A little-known Balkan species from Albania is transferred from the genus Odocnemis Allard, 1876 to the genus Nalassus Mulsant, 1854: Nalassus steindachneri (Apfelbeck, 1907), comb. n. The lectotype of this species is designated. External characters and features of male genitalia are shown and prove that this taxon belongs to the subgenus Horistelops Gozis, 1910. The distribution of Horistelops spp. in Europe is briefly discussed.